Evaluasi Kelayakan Media Komik Edukatif pada Materi Zat dan Perubahannya Berdasarkan Persepsi Mahasiswa Pendidikan Kimia - Setria Majuita; Afrizal Afrizal; Shabrina Shabrina (Jurnal Riset Pendidikan Kimia (JRPK), 2026)
Educational comic media has great potential in increasing learning motivation and conceptual understanding, but its use needs to go through a feasibility evaluation process before being implemented widely.This study aims to evaluate the feasibility of educational comic media on the topic of substances and their changes based on the perceptions of chemistry education students. The study used a quantitative approach with a survey method. The subjects were 30 Chemistry Education students at Jakarta State University who were selected using a total sampling technique. The research instrument was a questionnaire distributed via Google Form to measure several aspects of media feasibility, namely the feasibility of content, presentation and appearance, language, and usability or practicality of the media. Data were analyzed using descriptive statistics in the form of percentages to describe the tendency of respondents' perceptions. The results showed that educational comic media received very positive responses from students in all aspects of the assessment. In terms of content feasibility, the majority of respondents stated that they strongly agreed that the material in the comic was relevant, accurate, and in accordance with learning outcomes. The educational comic media that has been developed may still have shortcomings in terms of visual design, depth of material, or interactivity, so it still requires further improvement.